Perancangan Visual Kampanye "How to Value Creation in Modern Life" - Nurliana, Friska; Carl Louis Mawuntu, Refiero (Magenta | Official Journal STMK Trisakti, 2023)
This social campaign invented caused by the problem about creations that often happens because of lack of awareness and understanding of importance of appreciation of creation. Therefore the social campaign â€œHow to value creation in modern lifeâ€ are created. Using the literature research method from the journal and interview process at campaign targets and work activist that resulting a qualitative data between two party to be used for writing material as well as Main media results and supporting media on this visual campaign. So the solution that given from this campaign is the information about creations that would take a shape of infographic and motion graphic that would be shared in particular social media as well as other supporting media like webinar, poster, sticker, and pin button that designed so the information could reach the campaign target, that is young adult so it could get rid of the negative stigma about creations in society.